2010
DOI: 10.1111/j.1468-1331.2010.03312.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-anti-MAG DADS neuropathy as a variant of CIDP: clinical, electrophysiological, laboratory features and response to treatment in 10 cases

Abstract: DADS neuropathy without anti-MAG antibodies is more likely to be considered a variant of CIDP. In addition, such patients should be systematically investigated for an associated haematological or immunological condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 36 publications
2
58
1
3
Order By: Relevance
“…DADS associated with positivity for anti-MAG antibodies, termed anti-MAG neuropathy, is separated from CIDP according to the 2010 EFNS/PNS guidelines [3], [22]. In contrast, DADS without anti-MAG antibodies is often considered to be a variant of CIDP, and some reports have described differences in the response to immune treatment between DADS patients with and without anti-MAG antibodies [23], [24]. In the present study, we assessed the effects of sera obtained from three patients with DADS without anti-MAG antibodies, and found that the level of BNB damage after exposure to the sera from these patients was milder than that observed following exposure to the sera of the t-CIDP patients.…”
Section: Discussionmentioning
confidence: 99%
“…DADS associated with positivity for anti-MAG antibodies, termed anti-MAG neuropathy, is separated from CIDP according to the 2010 EFNS/PNS guidelines [3], [22]. In contrast, DADS without anti-MAG antibodies is often considered to be a variant of CIDP, and some reports have described differences in the response to immune treatment between DADS patients with and without anti-MAG antibodies [23], [24]. In the present study, we assessed the effects of sera obtained from three patients with DADS without anti-MAG antibodies, and found that the level of BNB damage after exposure to the sera from these patients was milder than that observed following exposure to the sera of the t-CIDP patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that DADS (without M) is a variant of CIDP and is truly distinct from DADS-M particularly in response to treatment [52]. One issue that remains unclear is whether DADS-M with anti-MAG antibodies is distinct from DADS-M without anti-MAG.…”
Section: Monoclonal Gammopathy Of Undetermined Significance (Mgus)mentioning
confidence: 92%
“…Patients who have an identical clinical and electrophysiologic phenotype but lack MAG antibodies can be classified as having DADS-CIDP36127; such patients may carry a better prognosis and respond more favorably to intravenous immunoglobulins, corticosteroids, and plasma exchange 127. The clinical hallmark of DADS neuropathy is the gradual onset of sensory ataxia resulting from impaired proprioception 128.…”
Section: Differential Diagnosis Of Sensory Ataxiamentioning
confidence: 99%